A Study of Structural Metaphor in Selected English Proverbs (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study examines structural metaphor as one of the three forms of conceptual metaphor established by Lakoff and Johnson (1980) in their book Metaphors We Live By: structural, orientational, and ontological metaphor. According to this idea, metaphor is more than just an aesthetic tactic employed by writers and poets to embellish and decorate their writings and poems; instead, they are logical structures reside in our brains to conceive more sophisticated features. As a result, metaphor is more than just a linguistic element; it is also an embodiment of human nature. Similarly, proverbs are verbal results of human experience and connection with nature or the world, and have been believed to be one of life's guidelines. This paper adopts Lakoff and Johnson (1980) and Kövecses (2010) models in which he divides conceptual metaphor into source and target domains. It aims at analysing proverbs by specifying the structural metaphors of the proverbs under study and identifying the source and target domains of these metaphors. Based on the data analysis, it was found that six out of the thirteen source domains and seven of the target domains identified by Kövecses (2010) were found in the study.